2020
DOI: 10.31195/ejejfs.696768
|View full text |Cite
|
Sign up to set email alerts
|

DNA barcoding, phytochemical screening and antimicrobial activity of Rhododendron arboreum, a high altitudinal medicinal plant from Nepal

Abstract: DNA barcoding has been proposed as a powerful taxonomic tool for species identification genetically. The Consortium for the Barcode of Life (CBOL) Plant Working Group has recommended the combination of rbcL & matK as the core plant barcode. Rhododendron of Nepal shows genetic diversity due to which 31 different species were reported till date, found in Nepal based on morphological character only. For the genetic identification first time, we collected different samples from the central and western parts of Nep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…Extracts of R. arboreum in Thailand have not been previously examined for their biochemical composition and bioactivity. The yield of the extracts was either higher than or comparable to that found in previous works (Nisar et al, 2011;Sonar et al, 2012;Bhandari & Rajbhandari, 2014;Sharma et al, 2020) while different extraction yields among the same plant parts were observed. Higher extraction yield of FF than DF suggested that the higher water concentration in the FF tissue was more effective for extraction and enhanced yield.…”
Section: Discussionsupporting
confidence: 80%
“…Extracts of R. arboreum in Thailand have not been previously examined for their biochemical composition and bioactivity. The yield of the extracts was either higher than or comparable to that found in previous works (Nisar et al, 2011;Sonar et al, 2012;Bhandari & Rajbhandari, 2014;Sharma et al, 2020) while different extraction yields among the same plant parts were observed. Higher extraction yield of FF than DF suggested that the higher water concentration in the FF tissue was more effective for extraction and enhanced yield.…”
Section: Discussionsupporting
confidence: 80%